The role of preschool in promoting children's healthy development: Evidence from an Australian population cohort - Goldfeld, S.; O'Connor, E.; O'Connor, M.; Sayers, M.; Moore, T.; Kvalsvig, A.; Brinkman, Sally (2016)
© 2015 Elsevier Inc. A growing body of evidence suggests that engagement with quality early childhood education and care (ECEC) programs such as preschool can enhance children's early development. The Australian Early Development Census (AEDC) provides a unique opportunity to explore the relationship between ECEC and children's developmental outcomes in a full population cohort of Australian school entrants. The AEDC is a teacher-rated checklist that provides data on ECEC experiences in the year before starting school, as well as five important domains of child development at school entry: physical health and wellbeing, social competence, emotional maturity, language and cognitive skills, and communication skills and general knowledge. In 2009, the AEDC was completed for 97.5% of Australian children in their first year of formal schooling (N = 261,147; M = 5 years, 7 months of age). Logistic regression analyses revealed that attendance at preschool was associated with reduced odds (OR = 0.69, p < 0.001 to OR = 0.40, p < 0.001) of being in the vulnerable range (<10th percentile) on four of the five AEDC domains (with the exception of emotional maturity; OR = 0.89, p = 0.002), compared to other ECEC experiences, or care exclusively by parents. Subsequent analyses revealed that this effect was evident for children living in both advantaged and disadvantaged communities. Together, the results suggest that engagement with preschool programs in Australia may present a plausible, equitable, and modifiable approach to improving children's developmental outcomes.